The Impact of Regional Integration in GVCs on Subsidy Allocation Among Manufacturing Firms in Russia - Юрий Вячеславович Симачёв; Анна Андреевна Федюнина; Игорь Михайлович Драпкин (Экономика региона)
While global demand for industrial policy-making continues to rise, increasing attention is being given to how these policies are shaped by participation in global value chains (GVCs), both in developed and developing countries. However, much of the research overlooks the regional dimension of support allocation, particularly the integration of regional economies into GVCs. This study aims to address this gap by examining the factors influencing state support at the regional level, with a focus on backward and forward linkages within GVCs in the manufacturing sector. The analysis is based on a survey of 1,900 Russian manufacturing firms conducted between August and November 2022, using data from 2019 to 2022 across various sectors and firm sizes. The findings show that Russian regional governments generally adopt conservative strategies when allocating financial support, focusing on a core group of companies crucial for maintaining regional economic stability. This support is primarily directed at exporters and firms fulfilling government contracts, with state-affiliated companies becoming the primary beneficiaries due to shifts in external conditions. Additionally, regions with greater integration into the global economy tend to adopt a more vertical policy approach, favoring large, GVC-integrated firms, while less integrated regions prioritize smaller firms, especially SMEs. Regions with stronger downstream linkages focus on supporting innovation-active firms to advance localization, import substitution, and technological independence goals. These findings highlight emerging priorities in Russia’s industrial policy, suggesting that regional initiatives are needed to strategically reposition the country’s regional economies in the global landscape amidst changing global dynamics.